Dental practitioners’ views on the need to treat developmental defects of enamel - Wong HM, McGrath C, Lo ECM, King NM. (Blackwell Synergy, 2007)
To assess dental practitioners’ views on the need to treat developmental defects of enamel (DDE). In addition, to identify factors associated with practitioners’ treatment decision (tooth factors and dentistrelated).